Implementasi Pembelajaran Berdiferensiasi Terintegrasi KSE untuk Meningkatkan Kualitas Pendidikan pada Kurikulum Merdeka melalui Kegiatan Webinar Optimalisasi Kinerja - Widyalistyorini, Dian; Yanti, Wiwin Fida; Endarwati, Sri; Nur Siyam, Isnaini; Alfi Muhimmah, Hitta (Universitas Pendidikan Indonesia Kampus Serang, 2025)
The implementation of differentiated learning that is integrated with the development of social-emotional competencies in the context of the Independent Curriculum in this webinar activity is to explore the strategies and approaches used by educators in maximizing differentiated learning to improve the quality of education. The main focus of this activity is to review how adaptive learning to students' needs can support their social-emotional development, which ultimately contributes to the formation of a generation that is better prepared to face life's challenges. Through key questions and interactive discussions, this webinar uncovered various best practices applied in the field, as well as the challenges faced by educators in implementing differentiated learning in the Independent Curriculum. The results mentioned that differentiated learning integrated with social-emotional competence has a positive influence on improving student learning motivation and student learning outcomes in the context of Merdeka Curriculum. It can be concluded that overall, the surveyed teachers often implement differentiated learning in their classrooms. The percentage figure is 82.3% which indicates a very high level of agreement with the integration of KSE in differentiated learning. Teachers must enhance and incorporate KSE to supports student development.